An outbreak of tuberculosis in Lleyn sheep in the UK associated with clinical signs. Issue 1 (11th July 2013) - van der Burgt, G. M.; Drummond, F.; Crawshaw, T.; Morris, S.
Abstract : This case report describes an outbreak of Mycobacterium bovis infection a Lleyn sheep flock associated with clinical signs of illthrift. There was no known direct contact with tuberculous cattle although bovine tuberculosis (bTB) is endemic in the area. The spoligotype isolated from the diseased sheep was the local spoligotype. The repeated use of the comparative intradermal tuberculin test, and the subsequent removal of reactor animals, resulted in apparent elimination of bTB from the flock. Lesions caused by M bovis in sheep may contain very few acid‐fast bacilli, and gross lesions may resemble those found in cases of Caseous Lymphadenitis. Routine meat inspection may, therefore, not always easily detect this notifiable disease.